2000
DOI: 10.3171/jns.2000.92.5.0771
|View full text |Cite
|
Sign up to set email alerts
|

Stent-assisted angioplasty of intracranial vertebrobasilar atherosclerosis: an initial experience

Abstract: Although primary intracranial VBA angioplasty with stent insertion is technically feasible, complications associated with the procedure can be life threatening. As experience is gained with this procedure, it may be offered routinely as an alternative therapy to patients with medically refractory posterior circulation occlusive disease that may develop into catastrophic VBA insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
61
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(63 citation statements)
references
References 20 publications
2
61
0
Order By: Relevance
“…8,11,12) However, only a few cases have been reported in which stent-assisted angioplasty for VA stenosis improved cerebral hypoperfusion and cognitive dysfunction. 9,11) Unfortunately, neither of these reports addressed the pathophysiology of cerebral perfusion, or described any cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,12) However, only a few cases have been reported in which stent-assisted angioplasty for VA stenosis improved cerebral hypoperfusion and cognitive dysfunction. 9,11) Unfortunately, neither of these reports addressed the pathophysiology of cerebral perfusion, or described any cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] In the present study, TAS for occluded lesions was shown to be technically feasible with a high success rate, similar to treatment of stenotic lesions. Technical success in treating the occluded lesion depends on the freshness of the occluded clots and the occluded segment being short enough for the microguidewire to pass through it; such conditions are frequently encountered in the acute stroke stage.…”
Section: Discussionmentioning
confidence: 82%
“…The procedure-related complication rate in the present study was higher than the reported rates in previous studies performed mainly for stenotic lesions and in the chronic stroke stage. [2][3][4][5][6][7][8][9][10] This may be because TAS for occluded lesions tends to induce distal embolism, intracranial hemorrhage involving hemorrhagic transformation and cerebral hyperperfusion syndrome, and vessel injury or rupture in comparison with the treatment of stenotic lesions. Because distal embolism tends to occur for a lesion crossed by a microguidewire, balloon catheter, or stent and is especially common with occluded lesions, the use of an embolic protection device with proximal flow control may reduce the incidence of this complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, intracranial PTAS has increasingly been used in clinical practice in the United States and other countries. [11][12][13][14][15][16][17][18][19] Currently, the self-expanding Wingspan stent (Boston Scientific) is the only device approved by the Food and Drug Administration (FDA) for use in patients with atherosclerotic intracranial arterial stenosis; it has been available since 2005 for the treatment of patients with 50 to 99% stenosis who have had a TIA or stroke while receiving antithrombotic therapy. 20 Because of uncertainty regarding the safety and efficacy of aggressive medical management alone as compared with aggressive medical management plus PTAS with the use of the Wingspan stent system, we began a randomized trial in November 2008 to compare these two treatments in highrisk patients with intracranial arterial stenosis.…”
mentioning
confidence: 99%